Value Chains of Public and Private Health-care Services in a Small EU Island State: A SWOT Analysis - Buttigieg, Sandra C.; Schuetz, Marcus; Bezzina, Frank (Frontiers in Public Health, 2016)
The global financial and macro-economic crisis of 2008/2009 and the ensuing recessions obliged policy makers to maximize use of resources and cut down on waste. Specifically in health care, governments started to explore ways of establishing collaborations between the public and private healthcare sectors. This is essential so as to ensure the best use of available resources, while securing quality of delivery of care, as well as health systems sustainability and resilience. This qualitative study explores complementary and mutual attributes in the value creation process to patients by the public and private health care systems in Malta, a small EU island state. A workshop was conducted with 28 professionals from both sectors to generate two separate value chains and this was followed by an analysis of strengths, weaknesses, opportunities and threats (SWOT). The latter revealed several strengths and opportunities, which can better equip health policy makers in the quest to maximize provision of health care services. Moreover, the analysis also highlighted areas of weaknesses in both sectors as well as current threats of the external environment that unless addressed, may threaten the state’s health care system sustainability and resilience to macroeconomic shocks. The study goes on to provide feasible recommendations aimed at maximizing provision of health care services in Malta.